PWE-019 An Evaluation Of Quantitative Faecal Immunochemical Tests For Haemoglobin. (9th June 2014) - Carroll, M; Piggott, C; Pearson, S; Seaman, HE; Bruce, H; Halloran, SP
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) in England provides biennial screening using a guaiac-based faecal occult blood test (gFOBT) for people aged 60–74 years. The European guidelines 1 recommend use of a quantitative faecal immunochemical test for haemoglobin (FIT) in population screening and the BCSP will replace gFOBT with FIT from 2016. The BCSP Southern Programme Hub (allied with the Guildford Medical Device Evaluation Centre) has evaluated FIT systems to guide future BCSP procurement. Four quantitative FIT systems suitable for population screening were evaluated: HM-JACKarc (Kyowa Medex Co. Ltd., Japan), NS-PLUS C15 Hb (Alfresa Pharma Corp., Japan), OC-SENSOR DIANA (Eiken Chemical Co. Ltd., Japan) and FOB Gold NG (Sentinel CH. SpA, Italy; analysed on a general chemistry analyser, BioMajesty, Jeol, Japan). Methods: The operation and technical performance of each system was assessed and compared with manufacturers' claims using the manufacturers' recommended sample collection tube loaded with haemoglobin (Hb)-spiked faecal samples or Hb in buffer. Results: All collection tubes and analysers were considered useable, although the BioMajesty was unnecessarily complex for a single analyte. The use of re-usable cuvettes by NS-PLUS, OC-SENSOR DIANA and BioMajesty increases the volume of water waste, but reduces plastic clinical waste. HM-JACKarc and NS-PLUS were the most analytically sensitive (accurately measures to the lowest concentration). Imprecision with NS-PLUS was inconsistent with manufacturers' claims; imprecision for OC-SENSOR DIANA and BioMajesty could not be compared directly with manufacturers' claims due to differences between mean concentrations of the samples. All analysers except BioMajesty demonstrated good linearity. Precision (variation of measurement) was good for HM-JACKarc and for OC-SENSOR DIANA within the manufacturers' recommended range. Automated or semi-automated dilution of highly concentrated samples was available with all analysers, except HM-JACKarc, which has a limited measurement range. The NS-PLUS and BioMajesty did not alert the user to a hook/prozone effect (erroneously low values at exceptionally high concentrations). Sample stability over a range of temperatures was similar to manufacturers' claims for all analysers and much improved from previous studies. Whilst fewer staff may be required for screening, they will need further laboratory training to process FIT samples. Conclusion: This evaluation provides essential information to guide the BCSP through the usual tendering procedure. Reference: Halloran SP et al . European guidelines for quality assurance in colorectal cancer screening and diagnosis. First Edition. Faecal occult blood testing. Endoscopy 2012;44(S03):SE65–SE87 Disclosure of Interest: None Declared.